Chapter I giorni della Memoria e del Ricordo. I viaggi di formazione nelle scuole toscane come Public History of Education - BRAVI, LUCA (Studi e saggi, 2019)
The construction of social cadres of memory is a process that is linked to the selection and oblivion of historical events, through a collective narrative aiming at building a sense of belonging and citizenship. Is it possible to get rid of public exploitation and travel through the places of 20th Century history to activate a path of correct historicization?